2009
DOI: 10.1039/b916898b
|View full text |Cite
|
Sign up to set email alerts
|

Active species of CeAl4 in the CeCl3-doped sodium aluminium hydride and its enhancement on reversible hydrogen storage performance

Abstract: By directly doping CeAl(4) into sodium aluminium hydride, which probably serves as the active species in the hydriding and dehydriding processes of CeCl(3)-doped NaAlH(4), a high reversible hydrogen capacity of 4.77-4.92 wt% (close to expected capacity of 5.13 wt%) can be achieved in less than 20 min under moderate conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 19 publications
3
42
1
1
Order By: Relevance
“…Recently it has been reported that Al 4 Ce is the catalytically active phase for CeCl 3 enhanced NaAlH 4 [20,21], which is further supported by the direct addition of Al 4 Ce to NaAlH 4 and CaAlH 4 [32]. The diffraction pattern of arc melted and milled Al 4 Ce in [21] is consistent with the reported structure type for Al 4 Ce [33].…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Recently it has been reported that Al 4 Ce is the catalytically active phase for CeCl 3 enhanced NaAlH 4 [20,21], which is further supported by the direct addition of Al 4 Ce to NaAlH 4 and CaAlH 4 [32]. The diffraction pattern of arc melted and milled Al 4 Ce in [21] is consistent with the reported structure type for Al 4 Ce [33].…”
Section: Resultssupporting
confidence: 84%
“…The hydrogen cycled NaH þ Al þ 0.02CeCl 3 sample in [20,21] clearly shows the broad Al 4 Ce doublet of (103)/(112) at the correct d-spacing (d ¼ 2.63 Å , or ca. 34 2q for Cu radiation), accurate to within 0.005 Å by interpolating the d-spacing axis directly from the diffraction patterns in [20,21] according to the well known d-spacing standard of the Al unit cell, a ¼ 4.049 Å .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations